Mesoporous Nickel-Based Zeolite Capsule Complex with Fe3O4 as Electrode for Advanced Supercapacitor. (19th December 2018) - Song, Lili; Han, Yinghui; Guo, Feng; Jiao, Yunpeng; Li, Yujuan; Liu, Yunpeng; Gao, Feng
Abstract : A new kind of zeolite capsule complex with ferriferous oxide (Fe3 O4 ) materials was prepared in this work. Its morphology was characterized via the scanning electron microscope (SEM), the high-resolution transmission electron microscopy (HRTEM), N2 adsorption analysis, and X-ray powder diffraction, respectively. The mesoporous nickel-based complex electrodes using substrate coating exhibited excellent energy storage properties through electrochemical testing. The high specific capacitance of 739.8 F g −1 was achieved at the current density of 1 A g −1 in a 6 M KOH solution. The good capacitance retention can retain 72.8% after 1000 cycles in a current density of 1 A g −1 . The energy storage mechanism of the nickel-based complex electrodes was also analyzed. Furthermore, the asymmetrical supercapacitors (ASCs) were fabricated using the zeolite capsule complex with Fe3 O4 as positive electrodes and the AC as negative electrodes, which performs high specific capacitance, outstanding energy density, superb power density, excellent cycle life, and small internal impedance. Those results suggest that the mesoporous nickel-based zeolite capsule complex with Fe3 O4 as an electrode would be an ideal candidate material for supercapacitor applications.